Optically Pure, Monodisperse cis‐Oligodiacetylenes: Aggregation‐Induced Chirality Enhancement1. Issue 1 (29th November 2013) - Chernick, Erin T.; Börzsönyi, Gabor; Steiner, Christian; Ammon, Maximilian; Gessner, David; Frühbeißer, Sabine; Gröhn, Franziska; Maier, Sabine; Tykwinski, Rik R.
Abstract Conformational changes in the conjugated backbone of poly‐ and oligodiacetylenes (PDAs and ODAs) play an important role in determining the electronic properties of these compounds. At the same time, conformational changes can also result in a folded structure that shows helical chirality. Using D‐camphor as a chiral building block, we have designed a high‐yielding, iterative synthesis of monodisperse, optically pure cis‐oligodiacetylenes (ODAs). cis‐ODAs up to the tridecamer have been formed, which is the longest monodisperse cis‐ODA reported to date. UV/Vis spectroscopy suggests a large effective conjugation length in THF, likely the result of a linear, planar conformation in this solvent. High‐resolution STM/AFM measurements of the nonamer cast from THF onto HOPG show a linear structure. In iPrOH, circular dichroism (CD) spectra suggest the formation of chiral aggregates for ODAs with at least nine D‐camphor units, based on a strong CD response.